2022
DOI: 10.5964/ejop.2607
|View full text |Cite
|
Sign up to set email alerts
|

Work addiction among employees and self-employed workers: An investigation based on the Italian version of the Bergen Work Addiction Scale

Abstract: The increasing interest in work addiction is connected to recent changes in the work culture and work habits. Despite this interest, knowledge pertaining to this phenomenon and measures to assess it are still limited. This study aims to contribute by examining the psychometric features of the Italian version of the Bergen Work Addiction Scale, a unidimensional scale based on the perspective of addiction. The research method consisted in two steps: in the first cross-sectional study, a convenience sample of 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…Our findings also suggested that the BWAS in its Arabic version has good reliability, with a Cronbach's alpha value of 0.811 for the total scores, corroborating the good psychometric characteristics of the original version of the BWAS which yielded alpha values of 0.80-0.84 (Andreassen et al, 2012a, b). Similar evidence of adequate reliability was also found in the Danish (α = 0.83) (Lichtenstein et al, 2019), Italian (α = 0.82) (Molino et al, 2021), Polish (α = 0.84) , and Turkish (α = 0.76) (Denizci Nazlıgül et al, 2021) validation studies. Overall, the present findings reinforce the ability of the Arabic version of the BWAS to evaluate the seven core elements of WA throughout a unidimensional measure, practical, and easy-to-use to detect WA in Arabic-speaking workers.…”
Section: Validation Of the Arabic Version Of The Bwassupporting
confidence: 74%
See 3 more Smart Citations
“…Our findings also suggested that the BWAS in its Arabic version has good reliability, with a Cronbach's alpha value of 0.811 for the total scores, corroborating the good psychometric characteristics of the original version of the BWAS which yielded alpha values of 0.80-0.84 (Andreassen et al, 2012a, b). Similar evidence of adequate reliability was also found in the Danish (α = 0.83) (Lichtenstein et al, 2019), Italian (α = 0.82) (Molino et al, 2021), Polish (α = 0.84) , and Turkish (α = 0.76) (Denizci Nazlıgül et al, 2021) validation studies. Overall, the present findings reinforce the ability of the Arabic version of the BWAS to evaluate the seven core elements of WA throughout a unidimensional measure, practical, and easy-to-use to detect WA in Arabic-speaking workers.…”
Section: Validation Of the Arabic Version Of The Bwassupporting
confidence: 74%
“…As we expected, the confirmatory factor analysis was able to replicate the 7-item one-factor structure of the BWAS found by Andreassen et al (2012a, b) in their original validation work in Western samples. Consistently, the unidimensional structure was also replicated in other validation works in Denmark (Lichtenstein et al, 2019), Turkey (Denizci Nazlıgül et al, 2021), and Italy (Molino et al, 2021), whereas a Polish study failed to support the original one-factor solution of the BWAS . Our findings also suggested that the BWAS in its Arabic version has good reliability, with a Cronbach's alpha value of 0.811 for the total scores, corroborating the good psychometric characteristics of the original version of the BWAS which yielded alpha values of 0.80-0.84 (Andreassen et al, 2012a, b).…”
Section: Validation Of the Arabic Version Of The Bwassupporting
confidence: 59%
See 2 more Smart Citations
“…Typically, individuals work long hours due to personal economic constraints or financial needs or excessive tasks and customer demands (workload). Ordinarily, it is not uncommon, in peculiar sectors, to discover predominantly established workaholics as a result of building up career growth for so many employees across human organisations(Molino et al, 2023). Hence, in light of the foregoing conceptual explanations and available data, this study put forward these hypotheses: H4.…”
mentioning
confidence: 88%